Inclusive School Practices: A look from the Physical Education (Revista horizonte, 2022)
Chilean education in the last time has suffered important modifications in search of equity, quality and inclusion raised in the General Law of Education, nevertheless, there are still practices that make exclusions. This is how, in a context of new demands, it is evident a lack of documents and a theoretical one on how to affront the school inclusion challenge, which justifies the importance of analysing practices that act as barriers and facilitators for successful inclusive processes in the various subjects. With this in mind, this research focused on the physical education classes, developed under a positivist paradigm with a quantitative approach, whose data were obtained by P direct observation. It was concluded that there is a greater number of practices that facilitate inclusion, in contrast to those that limit the learning and participation of students.